Evaluación de Escenarios de Descongestión Vehicular en Bogotá mediante Dinámica de Sistemas - Franco, Carlos; Mendez, Germán; Espitia, John (Ingeniería, 2015)
This paper proposes the development of a model based on system dynamics in which the transportation system in Bogotá D.C. is characterized. To do this the main variables involved in the transport system are modeled in order to achieve a global analysis of the problems of transportation and evaluate possible solutions proposed by different experts. The model is developed using the software Stella, and the different actors involved in global issues are included. Prior to the development of computational model is carried out data collection by experts on the subject, which shall provide an initial characterization, in order to understand the relationship between variables. Additionally six different alternative solutions to the problem are evaluated, to observe the impact that they would have on the transportation system.